Climate‐related trends in sapwood biophysical properties in two conifers: avoidance of hydraulic dysfunction through coordinated adjustments in xylem efficiency, safety and capacitance - BARNARD, DAVID M.; MEINZER, FREDERICK C.; LACHENBRUCH, BARBARA; MCCULLOH, KATHERINE A.; JOHNSON, DANIEL M.; WOODRUFF, DAVID R. (Plant, cell and environment, 2011)
ABSTRACT In the Pacific north‐west, the Cascade Mountain Range blocks much of the precipitation and maritime influence of the Pacific Ocean, resulting in distinct climates east and west of the mountains. The current study aimed to investigate relationships between water storage and transport properties in populations of Douglas‐fir (Pseudotsuga menziesii) and ponderosa pine (Pinus ponderosa) adapted to both climates. Sapwood thickness, capacitance, vulnerability to embolism, and axial and radial conductivity were measured on samples collected from trunks of mature trees. The sapwood of ponderosa pine was three to four times thicker than Douglas‐fir. Radial conductivity was higher in west‐side populations of both species, but axial conductivity was higher in the east‐side populations and in Douglas‐fir. Eastern populations of both species had sapwood that was more vulnerable to embolism than west‐side populations. Sapwood capacitance was similar between species, but was about twice as great in east‐side populations (580 kg m−3 MPa−1) as in west‐side populations (274 kg m−3 MPa−1). Capacitance was positively correlated with both mean embolism pressure and axial conductivity across species and populations, suggesting that coordinated adjustments in xylem efficiency, safety and water storage capacity may serve to avoid embolism along a gradient of increasing aridity.